VEGF blockade enhances the antitumor effect of BRAFV600E inhibition. Issue 2 (14th December 2016) - Comunanza, Valentina; Corà, Davide; Orso, Francesca; Consonni, Francesca Maria; Middonti, Emanuele; Di Nicolantonio, Federica; Buzdin, Anton; Sica, Antonio; Medico, Enzo; Sangiolo, Dario; Taverna, Daniela; Bussolino, Federico
Abstract: The development of resistance remains a major obstacle to long‐term disease control in cancer patients treated with targeted therapies. In BRAF‐mutant mouse models, we demonstrate that although targeted inhibition of either BRAF or VEGF initially suppresses the growth of BRAF‐mutant tumors, combined inhibition of both pathways results in apoptosis, long‐lasting tumor responses, reduction in lung colonization, and delayed onset of acquired resistance to the BRAF inhibitor PLX4720. As well as inducing tumor vascular normalization and ameliorating hypoxia, this approach induces remodeling of the extracellular matrix, infiltration of macrophages with an M1‐like phenotype, and reduction in cancer‐associated fibroblasts. At the molecular level, this therapeutic regimen results in a de novo transcriptional signature, which sustains and explains the observed efficacy with regard to cancer progression. Collectively, our findings offer new biological rationales for the management of clinical resistance to BRAF inhibitors based on the combination between BRAF V 600E inhibitors with anti‐angiogenic regimens. Synopsis: A combination of bevacizumab and vemurafenib analog PLX4720, which targets BRAF(V600E), sustains the decrease of tumor hypoxia, accumulation of antitumor macrophages, and reduction in cancer‐associated fibroblasts, delaying the onset of PLX4720 resistance. The association between a BRAF inhibitor with an antibody neutralizing VEGF induces a de novo genetic program, which is not observed in the presence of either agent alone. Provides a combinatorial benefit inducing an apoptotic program in cancer cells. Promotes vascular normalization improving tissue perfusion and oxygenation. Reprograms the tumor microenvironment promoting ECM remodeling and favoring M1‐like macrophage infiltration. Delays the onset of acquired resistance to the BRAF inhibitor. Abstract : A combination of bevacizumab and vemurafenib analog PLX4720, which targets BRAF(V600E), sustains the decrease of tumor hypoxia, accumulation of antitumor macrophages, and reduction in cancer‐associated fibroblasts, delaying the onset of PLX4720 resistance.